ANAC044 orchestrates mitochondrial stress signaling to trigger iron-induced stem cell death in root meristems - Juanmei Yan; Zhihang Feng; Yihui Xiao; Ming Zhou; Xiaobo Zhao; Xianyong Lin; Weiming Shi; Wolfgang Busch; Baohai Li (Proceedings of the National Academy of Sciences, 2025)
While iron (Fe) is essential for life and plays important roles for almost all growth related processes, it can trigger cell death in both animals and plants. However, the underlying mechanisms for Fe-induced cell death in plants remain largely unknown. S-nitrosoglutathione reductase (GSNOR) has previously been reported to regulate nitric oxide homeostasis to prevent Fe-induced cell death within root meristems. Here, we found that in the absence of GSNOR , exposure to high Fe treatment results in DNA damage–dependent cell death specifically in vascular stem cells in root meristems within 48 h. Through a series of time-course transcriptomic analyses, we unveil that in the absence of GSNOR , mitochondrial dysfunction emerges as the most prominent response to high Fe treatment. Consistently, the application of mitochondrial respiratory inhibitors leads to stem cell death in root meristems, and pharmacological blockage of the voltage-dependent anion channel that is responsible for the release of mitochondrial-derived molecules into the cytosol or genetic changes that abolish the ANAC017- and ANAC013-mediated mitochondrial retrograde signaling effectively eliminate Fe-induced stem cell death in gsnor root meristems. We further identify the nuclear transcription factor ANAC044 as a mediator of this mitochondrial retrograde signaling. Disruption of ANAC044 completely abolishes the GSNOR-dependent, Fe-induced stem cell death in root meristems, while ectopic expression of ANAC044 causes severe root stem cell death. Collectively, our findings reveal a mechanism responsible for initiating Fe-induced stem cell death in the root meristem, which is the ANAC044-mediated GSNOR-regulated mitochondrial stress signaling pathway.